Investigation and development of raintree furniture from the waste of urban tree - Hishammuddin, Ummu Aiman; Alli, Hassan (Academia Industry Networks, 2022)
The understanding of the benefit that has been provided by urban trees is important to justify the investment and improve stewardship. It has mostly been studied in environmental regulation and property values. However, a smaller number of researchers have taken into consideration on business perspective whereas the urban trees can be transformed as lumber and other solid-sawn wood product. Hence, this study aimed to investigate and develop furniture made from the waste of urban trees. The Raintree or Samanea saman is selected as a case study due to its greatest and fashionable urban tree species. The results recommended beautiful and uniqueness of Raintree wood properties. Besides that, the outcome also suggested as comprehensive management of urban trees resource attempt to increase the lumber value, while considering also other constraints on species selection, including biodiversity and suitability for urban environments.